Intervensi Kombinasi Deep Breathing Exercise dan Murottal terhadap Perubahan Nyeri dan Tanda-Tanda Vital Pasien Pasca Bedah Jantung Terbuka - Didit Supriyanto; Tintin Sukartini; Philia Setiawan; Asroful Hulam Zamroni; Siti Maimuna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of a combination of deep breathing exercises and murottal on changes in pain and vital signs in patients after open heart surgery in intensive care. This research method uses a quasi-experimental design pre-post test. The results showed that the difference test between the treatment and control groups, there was a significant difference. value= 0.001, SpO2 with p value=0.000 and MAP with p value=0.000. The statistical tests used are the Independent t-test, Paired t-test, and Manova, with a significance level of Î±= 0.05. In conclusion, combining deep breathing exercises and murottal is a relaxation technique that can affect changes in pain and vital signs (pulse, RR, SpOâ and MAP) in patients after open heart surgery. Keywords: Deep Breathing, Post-Cardiac Surgery, Vital Signs, Pain Level